(untitled) (The Harvest, 2022)
With the political shifts in twentieth century, South Asia has witnessed rapid socio-cultural and educational transformation. At this backdrop, the study aims to review the efforts made by South Asian countries for quality enhancement of teacher education recently. This thematic review of policy documents, reports, and articles representing eight countries revealed that though South Asia is rich with socio-cultural, economic, and topographical diversity, there are some convergence and divergence in terms of investment and environment offered to teacher education. For instance, Nepal, India, Sri Lanka, Maldives and Bhutan have provided better opportunities for teacher education and pre-service and in-service training and development, while teachers in Pakistan and Afghanistan have not made substantive progress. Except Pakistan and Afghanistan, all other countries have strict criteria for enrollment in teacher education programs, teacher recruitment, and licensing. These countries also provide motivating environment with the provisions of training and development, and awards and recognition. Whereas Pakistan and Afghanistan are facing two-fold challenges: nominal investment in teacher development and reconstructing the infrastructure damaged in decade-long armed struggle. The article concludes with the recommendation to increase investment in teacher education as developed and motivated teachers contribute to the overall transformation of education sector in South Asia.